An overview of in-class hours dedicated to English instruction in undergraduate language teacher education programs in Brazil: to be or not to be proficient? That is the question! - Godke, Ana Valeria Bisetto Bork; Retorta, Miriam Sester (Revista X, 2024)
The low proficiency in English among the Brazilian population is a concern addressed by various researchers (Rodrigues, 2022; De Souza Silva; Oliveira, 2022; David, 2016; British Council, 2014, 2015; Paiva, 2003; Brasil, 1998). Despite discussions about the quality of English education at the elementary and secondary levels, there is a gap in understanding the preparation of future English teachers in Brazilian higher education institutions. This study provides an overview of undergraduate programs in Portuguese/English and English in Brazil, emphasizing the hour load dedicated to formal language instruction. Based on the Common European Framework of Reference for Languages (CEFR, 2001) and studies on language proficiency of English teachers in different countries (Cinganotto, 2016; Roux, 2012; Uri; Aziz, 2018; Nagai; O’Dwyer, 2011), a quantitative study was conducted. Data were collected on the e-MEC platform and a descriptive statistical analysis was carried out. The study reveals that many undergraduate programs in Brazil lack adequate English language instruction. The low number of hours dedicated to English instruction in most programs prevents future teachers from becoming proficient enough to teach the language, potentially resulting in negative consequences for English language learning in the country.